PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA DINAS PENDIDIKAN KABUPATEN BANGLI - Putu Chintia Pramesti; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (VALUES, 2021)
The importance of transformational leadership style, organizational culture and work motivation to find out how far the employee's performance is in carrying out the assigned tasks. If employees have a transformational leadership style, organizational culture and high work motivation, the work results or performance will increase. This study aims to determine and obtain empirical evidence of the effect of transformational leadership style, organizational culture and work motivation on employee performance at the Bangli District Education Office. The population of this study were all employees at the Bangli District Education Office, totaling 30 employees. The sample in this study used a saturated sampling technique where all members of the population were sampled as many as 30 employees. The analytical tool used is multiple linear regression analysis. The results showed that the transformational leadership style variable had a positive and significant effect on employee performance. Organizational culture variables also have a positive and significant effect on employee performance. Work motivation variable has a positive and significant effect on employee performance.